2009
DOI: 10.1111/j.1365-2036.2009.04081.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the prevalence of idiopathic bile acid malabsorption as diagnosed by SeHCAT scanning in patients with diarrhoea‐predominant irritable bowel syndrome

Abstract: Summary Background  Recurrent, watery diarrhoea affects one‐third of patients diagnosed with irritable bowel syndrome (‘IBS‐D’). Idiopathic bile acid malabsorption (‘I‐BAM’) may be the cause. Aim  To determine the prevalence of I‐BAM in patients suffering from IBS‐D. Methods  A systematic search was performed of publications reporting patients presenting with IBS‐D type symptoms, who were subsequently confirmed as having I‐BAM by SeHCAT scanning. Results  Eighteen relevant studies, 15 prospective, comprising 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
351
0
25

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(385 citation statements)
references
References 23 publications
(42 reference statements)
9
351
0
25
Order By: Relevance
“…Nevertheless, other studies have demonstrated a beneficial response to open treatment, particularly in those with moderate to severe BAD. 17,23 A systematic review noted that response to colestyramine occurred in 96% of patients with 75 SeHCAT retention <5%, 80% with 75 SeHCAT retention <10%, and 70% with 75 SeHCAT retention <15%. 23 In our study, of those that had BAD, 28.6% were mild, 28.6% moderate and 42.8% severe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, other studies have demonstrated a beneficial response to open treatment, particularly in those with moderate to severe BAD. 17,23 A systematic review noted that response to colestyramine occurred in 96% of patients with 75 SeHCAT retention <5%, 80% with 75 SeHCAT retention <10%, and 70% with 75 SeHCAT retention <15%. 23 In our study, of those that had BAD, 28.6% were mild, 28.6% moderate and 42.8% severe.…”
Section: Discussionmentioning
confidence: 99%
“…17,23 A systematic review noted that response to colestyramine occurred in 96% of patients with 75 SeHCAT retention <5%, 80% with 75 SeHCAT retention <10%, and 70% with 75 SeHCAT retention <15%. 23 In our study, of those that had BAD, 28.6% were mild, 28.6% moderate and 42.8% severe. This suggests that making a positive diagnosis will be of clinical benefit, and serves as a mandate for randomized placebo-controlled trials of bile acid sequestrants in D-IBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Individuals with IBS are more likely to consume health care resources than healthy individuals, 8 with up to 80% of sufferers consulting their primary care physician as a result of symptoms. 9,10 Diagnosing IBS can be challenging due to overlap between the symptoms that sufferers report and those of organic GI conditions such as celiac disease, [11][12][13] small intestinal bacterial overgrowth, 14 bile acid diarrhea, 15,16 exocrine pancreatic insufficiency, 17 or inflammatory bowel disease. 18 Partly as a result of this uncertainty, symptom-based diagnostic criteria were developed for use by physicians consulting with patients with suspected IBS as early as the 1970s, with Manning et al reporting six symptoms that were commoner among individuals found ultimately to have IBS after investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the prevalence of bile acid malabsorption suggest this may be a common cause of IBS-D symptoms (up to one in four cases), and targeted therapeutic intervention with a bile acid binder (e.g. cholestyramine) may be warranted [21,22].…”
Section: Organic Disease and Fgid Symptomsmentioning
confidence: 99%